Finder-ICET: sistema web de achados e perdidos para o campus ICET/UFAM - Silva, Daniele Vasconcelos da (Brasil, 2024)
Information and Communication Technology has contributed over the years to numerous transformations in society, including the creation of online lost and found platforms. In this context, the academic community of the Institute of Exact Sciences and Technology faces difficulties in disseminating and efficiently managing lost and found items on campus, requiring a technological solution to facilitate the return of items to their owners. This work aims to develop a web system that allows for the dissemination and management of found and lost items at the university. The methodology of the work consisted of the stages of Literature Review, Initial Proposal, and Development and Evaluation. The results obtained in the evaluation were positive, demonstrating a high level of acceptance among the target audience, with 88.9% of the evaluators fully agreeing that the system will be useful for the academic community, and 88.9% who intend to use the system if they have access.